The impact of different encouragement strategies on performance during maximal aerobic exercise tests: A scoping review - Ketelhut, S.; Turuani, G.; Möhle, M. (International Journal of Sports Physiology and Performance, 2025)
Maximal aerobic exercise tests (MAET) are essential in sports and clinical settings for assessing fitness and guiding treatments. Encouragement strategies play a crucial role in ensuring maximal effort, thereby enhancing test validity. This scoping review aimed to examine the effects of various encouragement strategies on performance outcomes during MAET. This review followed the Guidelines and Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews protocols. A comprehensive search was conducted across multiple databases (Google Scholar, PubMed, PsycINFO, SURF, SPONET, and Taylor & Francis) using a combination of keywords related to MAET and encouragement strategies. Studies were eligible if they assessed the effects of MAET with at least 1 motivational strategy and were published in English in peer-reviewed journals. Data were extracted independently by 2 reviewers, with disagreements resolved through a third reviewer. Forty-nine studies were included in this review. The studies assessed various encouragement strategies including music (41%), verbal encouragement (12%), self-talk (21%), competition (10%), and attentional focus (16%) across both open- and closed-ended MAET. Music and sound consistently improved performance in open-ended tests (no predetermined end), whereas their effects in closed-ended tests (defined start and end point) were inconsistent. Verbal encouragement, particularly when frequent and personalized, generally enhanced performance. Positive effects were also observed for motivational self-talk and competitive conditions. However, the effects of attentional focus strategies remained inconclusive. This review highlights the potential of different encouragement strategies in enhancing performance during MAET. However, gaps remain in understanding their mechanisms, and future research should focus on combining strategies and standardizing protocols.